2008
DOI: 10.1261/rna.819308
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic analysis of T-box regulatory systems in bacteria

Abstract: T-box antitermination is one of the main mechanisms of regulation of genes involved in amino acid metabolism in Gram-positive bacteria. T-box regulatory sites consist of conserved sequence and RNA secondary structure elements. Using a set of known Tbox sites, we constructed the common pattern and used it to scan available bacterial genomes. New T-boxes were found in various Gram-positive bacteria, some Gram-negative bacteria (d-proteobacteria), and some other bacterial groups (Deinococcales/Thermales, Chlorofl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
223
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 124 publications
(240 citation statements)
references
References 76 publications
12
223
0
2
Order By: Relevance
“…Although proline-responsive T-box systems are predicted to occur widely in Gram-positive bacteria (Gutiérrez-Preciado et al, 2009;Vitreschak et al, 2008;Wels et al, 2008), the data reported here on the regulation of the proBA and proI genes of B. subtilis provide, to the best of our knowledge, the first experimental proof for the functionality of a proline-responsive T-box system in any micro-organism.…”
Section: Introductionmentioning
confidence: 63%
See 3 more Smart Citations
“…Although proline-responsive T-box systems are predicted to occur widely in Gram-positive bacteria (Gutiérrez-Preciado et al, 2009;Vitreschak et al, 2008;Wels et al, 2008), the data reported here on the regulation of the proBA and proI genes of B. subtilis provide, to the best of our knowledge, the first experimental proof for the functionality of a proline-responsive T-box system in any micro-organism.…”
Section: Introductionmentioning
confidence: 63%
“…T-box systems are widespread in Gram-positive bacteria, and are sensory and regulatory devices that prevent wasteful overproduction and overaccumulation of amino acids (Green et al, 2010;Gutiérrez-Preciado et al, 2009;Vitreschak et al, 2008;Wels et al, 2008;Winkler, 2007). Tbox systems are RNA-based regulatory switches (Henkin, 2008) that are used in many Gram-positive microorganisms to regulate the expression of aminoacyl-tRNA synthetase genes and of genes involved in amino acid biosynthesis and uptake (Green et al, 2010;Gutiérrez-Preciado et al, 2009;Winkler, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…82 The tRNA Gly UCC is also predicted to bind to the 5′-GGA-3′ Specifier codon in Bacillus and Staphylococcus species glycyl T-box riboswitches. 83 …”
Section: Unmodified Wobble Position 34 and The Importance Of Position 32mentioning
confidence: 99%